PENGARUH PENERAPAN METODE KOMIDI PUTAR DISKUSI TERHADAP MINAT BELAJAR IPA SISWA SDN - Nurhayati Selvi (Journal of Educational Science and Technology (EST), 2016)
This study aims to (1) know the description of implementation methods carousel discussion; (2) know the description of interest in learning science before and after the discussion carousel method; (3) the effect of the application of methods carousel discussion towards interest in learning science. Methods used Tru Experiment Design with design pretest-possttest control group design. The technique of collecting data through questionnaires interest, observation and interviews. Its population is a whole class of elementary school SDN KIP Maccini Makassar 2014-2015 school year as many as 66 people. Mechanical Sampling was stratified random sampling, obtained as many as 56 people. Data analysis technique used is descriptive and inferential analysis. The results showed that the application of the carousel discussion method comprising the step of grouping students, forming two concentric circles, conversations and conclusions are generally performing well. Siwa learning interest in learning science before implementation of the method carousel discussion is in the category of low and medium, the experimental group or the control group. There is increasing interest in students in the high category in the experimental group after a given method carousel discussion while the control group the medium category. Use of the method carousel discussion affect the interest to learn science.